Hubungan lama menderita hipertensi dengan kejadian stroke - Aprilia, Helen; Triswanti, Nia; Pratama, Sandhy Arya; Suryawan, Boby (JOURNAL OF Qualitative Health Research & Case Studies Reports, 2026)
Background: Hypertension is a major risk factor for stroke, a condition caused by impaired cerebral blood flow due to vascular occlusion or hemorrhage. Prolonged hypertension results in progressive vascular damage, including atherosclerosis and vascular remodeling, which cumulatively increases the risk of stroke. Purpose: To determine the correlation between the duration of hypertension and stroke incidence. Method: This study used a quantitative analytical cross-sectional design. Based on inclusion and exclusion criteria, a sample of 211 individuals was obtained. Data analysis was performed using the chi-square statistical test. Results: Among the respondents, 151 (71.6%) had hypertension for ≥ 5 years, and 37 (17.5%) had experienced a stroke. There was a significant association between the duration of hypertension and stroke incidence (P-value = 0.005). Conclusion: There was a significant association between the duration of hypertension and stroke incidence.   Keywords: Duration of Hypertension; Hypertension; Stroke.   Pendahuluan: Hipertensi merupakan faktor risiko utama stroke, suatu kondisi yang disebabkan oleh gangguan aliran darah otak akibat oklusi vaskular atau perdarahan. Durasi hipertensi yang berkepanjangan mengakibatkan kerusakan vaskular progresif, termasuk aterosklerosis dan remodeling vaskular, yang secara kumulatif meningkatkan risiko stroke. Tujuan: Untuk mengetahui korelasi antara Durasi Hipertensi dan Insidensi Stroke Metode: Jenis penelitian yang digunakan adalah analitik kuantitatif dengan desain cross-sectional. Berdasarkan kriteria inklusi dan eksklusi, diperoleh sampel sebanyak 211 orang. Analisis data dilakukan menggunakan uji statistik chi-square. Hasil: Ditemukan bahwa di antara responden, 151 (71.6%) memiliki durasi hipertensi ≥ 5 tahun dan 37 (17.5%) pernah mengalami stroke. Terdapat hubungan yang signifikan antara durasi hipertensi dan kejadian stroke (nilai P = 0,005). Simpulan: Terdapat hubungan yang signifikan antara durasi hipertensi dan kejadian stroke.   Kata Kunci: Hipertensi; Lama menderita; Stroke.